Participation in conferences, scientific-practical seminars, round tables as an effective form of scientific work in university - Сопілко, І. М.; Череватюк, В Б. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article it comes to a form of implementation of scientific activity in university, which is related toparticipation of teachers and students.